EXAMINING THE RELATIONSHIP BETWEEN DESTINATION LOYALTY AND MARKETING IN TOURISM: INSIGHTS FROM STRUCTURAL EQUATION MODELING (Scientific Journal of Actuarial Finance and Accounting, 2025)
The goal of this study is to conduct a systematic literature review on tourism, including how to reach loyal tourists and develop marketing activities. The analysis used only articles from the Scopus database (2010-2024) and was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Appropriate criteria were set for the final analysis, and 38 publications (only articles) were selected based on them. According to the results, during the given period, the number of articles related to the field was up to 5 published annually, except for 8 articles published in 2020. The journal "Tourism Management" received 606 citations for its only article, making it the most influential journal in this field. This work contains valuable information on the directions for future research in analysing the main factors influencing destination loyalty. Also, several keywords such as "destination loyalty", "tourist satisfaction", "destination image", "marketing" and "structural equation modeling" are popular and used with a wide range of keywords.